Carta a Gordito - Palabra Obrera (My University, 1960)
Equipo - Congreso - UOM régimen electoral.
Keywords: Palabra Obrera; Regionales - Córdoba; Metalúrgicos; Congreso Palabra Obrera, II; Organización